Myocardial reverse remodeling after pressure unloading is associated with maintained cardiac mechanoenergetics in a rat model of left ventricular hypertrophy - Ruppert, Mihály; Korkmaz-İçöz, Sevil; Li, Shiliang; Németh, Balázs Tamás; Hegedűs, Péter; Brlecic, Paige; Mátyás, Csaba; Zorn, Markus; Merkely, Béla; Karck, Matthias; Radovits, Tamás; Szabó, Gábor (American journal of physiology. Heart and circulatory physiology, 2016)
Pressure unloading represents the only effective therapy in increased afterload-induced left ventricular hypertrophy (LVH) as it leads to myocardial reverse remodeling (reduction of increased left ventricular mass, attenuated myocardial fibrosis) and preserved cardiac function. However, the effect of myocardial reverse remodeling on cardiac mechanoenergetics has not been elucidated. Therefore, we aimed to provide a detailed hemodynamic characterization in a rat model of LVH undergoing pressure unloading.
Gesehen am 06.05.2020